Appraisal of coral bleaching thresholds and thermal projections for the northern Red Sea refugia - Eladawy, Ahmed; Nakamura, Takashi; Shaltout, Mohamed; Mohammed, Asmaa; Nadaoka, Kazuo; Fox, Michael D.; Osman, Eslam O. (Frontiers in Marine Science, 2022)
Corals in the northern Red Sea exhibit high thermal tolerance despite experiencing frequent and severe heat stress. It is assumed that corals in the Red Sea have similar bleaching thresholds (32°C), and thus, the apparent bleaching tolerance of corals in the NRS is due to the lower ambient temperature (25–28°C) of the region that remains under their physiological maxima. Whether bleaching patterns along the Red Sea are independent of the local maximum monthly mean and aligned with the proposed 32°C threshold has yet to be determined. Here, we used surface seawater temperature remote sensing data (1982–2020) to model spatial distributions of Degree Heat Weeks across the Red Sea using coral thermal threshold values of 30, 31, and 32°C. We also used the Coupled Model Intercomparison Project Phase 5 model outputs to predict warming trends in the Red Sea under different representative concentration pathway scenarios. Our data show the 32°C–adjusted thresholds dramatically reduced Degree Heat Weeks in the northern Red Sea, but not in central or southern Red Sea, which is consistent with bleaching observations throughout the Red Sea. Further, it is predicted that the northern Red Sea will experience the least range of warming by end of the 21st century (2–2.5°C) compared to the central and southern regions (2.7-3.1°C) under the business as usual scenario. The slower rate of warming in the northern Red Sea should help promote the refugia (i.e., the ability to maintain favorable temperature for corals) to remain functional for decades. Collectively, our results support the hypothesis that coral bleaching thresholds are independent of the local maximum monthly mean, and corals have similar thresholds throughout the Red Sea. Regional projections of warming suggest that the northern Red Sea that experiences low ambient surface seawater temperature and maximum monthly mean will not reach the proposed threshold (32°C) by end of the 21st century. Our work suggests that while global warming intensifies, corals in the northern Red Sea may be some of the last standing corals.